Incidence of imposex in marine gastropod Canarium urceus (Linnaeus, 1758) collected from Cantilan Public Market, Cantilan, Surigao del Sur - Enhaynes, Phoebe L.; Silapan, Judith R. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2021)
The biofouling problem faced by the shipping industry is often controlled by using antifouling paints with tributyltin (TBT). However, TBT affects gastropods in that it induces the growth of a penis in female gastropods and this condition is called imposex. To assess the incidence of imposex, samples of the conch Canarium urceus was collected from the Cantilan Public market and the length and weight of the collected samples were measured according to its sex. The incidence of imposex was calculated and was compared to the research of Agan in 2017. No imposex has been observed in this study as opposed to Agan in which 12.5 % incidence of imposex was observed in the sampling site near the shipyard. This could be attributed to the proximity of the sampling site to the shipyards. There is a significant difference at P < 0.05 between the mean length of 46.7 mm and 43.1 mm in females and males, respectively. There is also a significant difference at P < 0.05 between the mean weight of 6.8 g and 5.2 g in females and males, respectively. There was also a strong positive correlation between length and weight among the samples collected from the market.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2021.